Lapangan Gunung Api Tersier Daerah Berbah Sleman - Imogiri Bantul,Yogyakarta - , G. Hartono ([Yogyakarta] : Departemnts of Geological Engineering Faculty of E, 2009)
In the area of Berbah - Sleman to Imogiri - Bantul Districts, Yogyakarta Tertiary volcanic rocksform a hummocky topography. Those volcanic rocks comprise coherent lavas and volcaniclastic rocks having basalt to basaltic andesite in composition. Genetically, the rocks are pillow lavaflows, dikes. pyroclastics and resedimented (syn-eruptive) deposits. Previous workers stated that the hummocky topography was controlled by tectonic faulting. Based on volcanic geology study it is believed that the landscape is a volcanic field consisting some paleo volcanic cones. The volcanic field is distributed in NE-SW direction. Perhaps, this pattern was controlled by a subsurface fault. and then reactivated to cut the volcanic cones. Volcanic activities in this area varied from monogenetic cones, such as Watuadeg paleovolcano, developing to the Sudimoro composite volcano.